Roland Barthes, the filmic versus cinema. The suspended sense as definition of cinematic modernity - Monterrubio Ibáñez, Lourdes (Escritura e Imagen, 2021)
This article aims to analyse Roland Barthes’ texts on film practice. His resistance to cinema, linked to his autobiographical writing, is revealed as the impossibility of fetishizing the moving image, which must then be reduced to the photographic, thus defining the obtuse sense. However, through the conception of suspended sense, Barthes detected the emergence of cinematic modernity that, precisely, was capable of overcoming this limit; that is to say, to destroy the action-image and its temporality without stopping its movement. The choice of works by Buñuel, Bergman, Resnais, Pasolini and Antonioni establishes a conception of the suspended sense linked to the suspension of temporality and estrangement that prefigure the Deleuzian time-image. Barthes finds in modern cinema the blind spot of his analytical capacity, that of an image that suspends sense without stopping its movement.
Keywords: Roland Barthes; suspended sense; cinematic modernity; time-image